Programas de intervenção para crianças, adolescentes e pais a vivenciar cancro parental: Protocolo de scoping review - Lomba, Maria de Lurdes Lopes de Freitas (2021)
Background: Parental cancer affects children, adolescents, and the family unit. The implementation of intervention programs leads to the development of parental skills and positive outcomes for children in terms of understanding their parents' cancer, developing coping mechanisms, improving parent-child communication and relationships, and empowering the family to cope with cancer. Objective: To map the available intervention programs for children, adolescents, and parents experi- encing parental cancer (patients with cancer). Review method: Scoping review methodology proposed by the Joanna Briggs Institute. The process of data analysis, extraction, and synthesis will be performed by independent reviewers. Presentation and interpretation of results: Mapping the programs will allow identifying the interven- tions developed by health professionals for children, adolescents, and parents experiencing parental cancer. Conclusion: The review resulting from this protocol will allow selecting the best interventions for designing a nursing intervention program for adolescents and parents experiencing parental cancer.